Psychogeography - Providing a lens on corporate culture and its potential impact on career success: A novel and efficient approach - Wardale, D.; Lord, Linley (Management Centre International, 2017)
Â© ACPIL. Psychogeography refers to the loose interface between psychology and geography. Specifically it examines how we impact on the environment and the environment impacts on us. As a process it involves intimately observing the environment and seeing what may have been previously unobserved. Participants then construct meaning from these observations. This paper describes how we used a time-limited psychogeography approach followed immediately by a focus group as research method. The aim was to determine if examining participants' work environment would potentially enable them to identify enablers and barriers to career success. The findings from these two short interventions are compared to the more often used semi-structured interview approach to reveal that the psychogeography provided another lens to the research. Interestingly factors that were uncovered in the psychogeography and focus groups were generally different to those identified in the interviews. The participants were a group of high-potential academic women at a large public university in Western Australia. They were enrolled in a career and leadership development program aimed at assisting women access promotions and other senior roles leadership within the university Much of the women's career development literature focuses on 'fixing women' and not the system. To that end we wanted to use a method, in addition to interview questions, to uncover aspects of the corporate environment that might impact on women's decisions to progress their careers. We asked participants to dÃ©rive, stroll or wander within their university campus with a view to observing any 'career enablers and barriers at work'. To not impose any further burden on their time, and to manage the wealth of data generated by the psychogeography, we asked the women to immediately share their insights through a structured focus group discussion. Participants found the psychogeography exercise a novel approach to discovering and rediscovering their work environment. The findings revealed aspects of the work environment that had not previously been overt. These included participants' appreciation of students having fun and a carnival atmosphere within the campus yet a simultaneous concern at the lack of quiet spaces to support scholarship and research; a disparity of investment in infrastructure improvements across various schools and faculties, which led to discussions of how disparately workload was managed by different managers; staffbeing segregated from students and other staffwith security doors; the number of steps at the university and the impact this would have on some people with a disability. One pleasing and unexpected outcome of the psychogeography exercise was the level of energy and collegiality it generated. The exercise was conducted at an early stage in an eight-month career development program and its use heightened participant's awareness of aspects of their work environment's impact on career success that may have otherwise remained uncovered or unexamined. Our view is that psychogeography; within a limited timeframe is a valuable method to employ. When the data from such a method is captured though a focus group the impost on participant' times is lessened, the quality of data is retained with the combined research method producing novel findings that may be different to other more traditional qualitative research methods. In our case, they helped uncover aspects of university culture and enculturation to which many research participants had been previously oblivious.